Detection of Cutting Agents in Drug‐Positive Seized Exhibits within the United States. Issue 3 (28th November 2018) - Fiorentin, Taís R.; Krotulski, Alex J.; Martin, David M.; Browne, Thom; Triplett, Jeremy; Conti, Trisha; Logan, Barry K.
Abstract: The following report summarizes a study performed on seized drug exhibits collected in two U.S. states to evaluate the presence and identification of cutting agents. Aliquots of seized drug materials from Kentucky ( n = 200) and Vermont ( n = 315) were prepared using a dilute‐and‐shoot procedure. Initial analysis was performed using gas chromatography–mass spectrometry (GC‐MS) followed by analysis using liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐QTOF). Active compounds detected overall included caffeine (31.0%), quinine/quinidine (24.7%), levamisole (11.6%), acetaminophen, (8.2%) and procaine (8.2%). These compounds were found with several drugs of abuse, such as heroin, fentanyl, methamphetamine, and cocaine. This novel information about cutting agents used to dilute or alter drugs of abuse is important to criminal investigations and in the management of acute intoxications at health centers. However, common methodologies for analysis and standard reporting practices frequently do not include cutting agents, resulting in lacking or inadequate information regarding prevalence of these substances.